Patient Perspectives on Anti-spike Monoclonal Antibody Therapy for Mild to Moderate Coronavirus Disease-2019 - Raymund R Razonable MD; Ravindra Ganesh MBBS, MD; Rachel K Bishop RN; Tracy L Culbertson MSN, RN; Molly Destro Borgen MA; Michelle C Hedin MSN, RN; Laura H Hopkins RN; Tammy A Jackson RN; Jennifer J Larsen MSN, RN; Jennifer A Matoush APRN, MS; Darcie E Moehnke MAN, RN; Shelly M Olson MSN, RN; et al. (Journal of Patient Experience, 2022)
Anti-spike monoclonal antibodies emerged as effective early treatment of high-risk individuals with mild-to-moderate COVID-19. Although their clinical and safety outcomes have been reported, patient perspectives of these experimental therapies have not been evaluated. In this survey participated by 644/2412 (26.7% response) individuals evaluated for anti-spike monoclonal antibody therapies, the majority of 523 patients who received the antibody infusion were very satisfied with their overall patient experience, the quality of care provided, and various aspects of medical care. They voiced satisfaction with the communication with providers before and during treatment, including education provided about monoclonal antibody treatment, the potential benefits and adverse effects, detailed instructions on the process of infusion, and safety protocols employed at the infusion facilities. Nearly a quarter (23.6%) of 121 patients who declined therapy indicated they would accept treatment should it be offered again. These patient perspectives may be used to guide healthcare facilities and providers in optimizing the care provided to high-risk outpatients with COVID-19.